A RACIONALIZAÇÃO PROCESSUAL CIVIL PREVISTA NA LEI Nº 14.195, DE 21 DE AGOSTO DE 2021 – BREVES COMENTÁRIOS ÀS ALTERAÇÕES NO CPC - Nogueira, Daniel Moura (Revista da AJURIS - Qualis A2, 2023)
THE CIVIL PROCEDURAL RATIONALIZATION PROVIDED FOR IN LAW 14,195 OF AUGUST 21, 2021 – BRIEF COMMENTS ON THE CHANGES IN THE CPC ÁREA(S): direito processual civil. RESUMO: O ensaio estuda a reforma do CPC de 2021, que alterou, substancialmente, suas regras fundamentais. As modificações foram tanto no processo de conhecimento quanto no de execução, alterando elementos desde prazos e formas até prescrição intercorrente. Essas alterações entraram em vigor de imediato, erigindo tumulto pragmático no sistema. Aqui analisa as alterações de forma hermenêutica crítica e prática, com uma conclusão pragmática. ABSTRACT: The essay studies the 2021 CPC reform, which substantially changed its fundamental rules. The changes were in the process of knowledge and execution, changing elements from deadlines and forms to intercurrent prescription. These changes took effect immediately, creating pragmatic turmoil in the system. Here it analyzes the changes in a critical and practical hermeneutic way, with a pragmatic conclusion. PALAVRAS-CHAVE: processo civil; procedimentos; formas; prazos; citação; prescrição; inconstitucionalidade. KEYWORDS: civil procedure; procedures; shapes; deadlines; quote; prescription; unconstitutionality. SUMÁRIO: Introdução; 1 Novo comportamento das partes; 2 Mais uma regra de contagem de prazo; 3 Novo prazo para o Judiciário promover a citação; 4 Nova forma/regra para citação, deveres das partes e consequências; 5 Exceções ao cadastro obrigatório de pessoa jurídica e compartilhamento entre órgãos; 6 Exceções à nova forma/regra para citação; 7 Nova forma do pedido da prova de exibição de documento ou coisa; 8 Suspensão do processo de execução e prescrição intercorrente; 9 Extensão do tema ao cumprimento de sentença; 10 Da eficácia da norma no tempo; 11 (In)Constitucionalidade das alterações do CPC; Referências. SUMMARY: Introduction; 1 New behavior of the parties; 2 One more term counting rule; 3 New deadline for the judiciary to promote the summons; 4 New form/rule for citation, duties of the parties and consequences; 5 Exceptions to the mandatory registration of legal entities and sharing between bodies; 6 Exceptions to the new form/rule for citation; 7 New form of request for proof of document or thing; 8 Suspension of the execution process and intercurrent prescription; 9 Extension of the subject to the execution of the sentence; 10 Effectiveness of the norm over time; 11 (In)Constitutionality of the CPC amendments; References.